Ethel Armes collection of Lee family papers - Armes, Ethel, 1876-1945.; Carter, Lucy Grymes Lee, 1786-1860.; Corbin, Hannah Lee, 1728-1782.; Hopkins, Cornelia Lee, 1780-1815.; Izard, Elizabeth Byrd Carter Shippen; Lee, Ann Hill Carter, 1773-1829.; Lee, Anne Robinson McCarty, 1798-1840.; Lee, Charles Carter, 1798-1871.; Lee, Elizabeth Collins, -1858.; Lee, Henry, 1756-1818.; Lee, Henry, 1787-1837.; Lee, Mary Randolph Custis, 1807-1873.; et al.
Correspondence, architectural plans, genealogical papers, maps, legal papers, clippings, and other materials assembled by Armes in preparing her book, Stratford Hall: The Great House of the Lees (1936). Lee family members represented include Lucy Grymes Lee Carter, Hannah Lee Corbin, Elizabeth Shippen Izard, Ann Hill Carter Lee, Ann R. McCarty Lee, Charles Carter Lee, Cornelia Lee Hopkins, Elizabeth Collins Lee, Henry ("Lighthorse Harry") Lee, Henry ("Black Harry") Lee, Mary Custis Lee, Richard Bland Lee, Richard Henry Lee, Robert E. Lee, Thomas Lee, Alice Lee Shippen, Anne Shippen Livingston, Thomas Lee Shippen, and William Shippen. Includes material relating to the Revolution, politics, agriculture, slavery, family life, and Shirley Plantation (Va.). Prominent correspondents include Duff Green, Nathanael Greene, Alexander Hamilton, James Madison, Franklin D. Roosevelt, John Tyler, and George Washington.
Chiefly photocopies and transcripts of originals in various repositories.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Green, Duff, -- 1791-1875 -- Correspondence; Greene Nathanael, -- 1742-1786 -- Correspondence; Hamilton, Alexander, -- 1757-1804 -- Correspondence; Madison, James, -- 1751-1836 -- Correspondence; Roosevelt, Franklin D. -- 1882-1945 -- Correspondence; Tyler, John, -- 1790-1862 -- Correspondence; Washington, George, -- 1732-1799 -- Correspondence; Lee family; Agriculture -- Virginia; Plantations -- Virginia; Slavery -- Virginia; Shirley Plantation (Va.); Stratford Hall (Va.); United States -- History -- Revolution, 1775-1783.; Virginia -- Social life and customs